Description of Postural Balance of The Body of Elderly Age based on Age Category 45-90 Years - Sari, Etik Yunita; Komalasari, Dwi Rosella (Academic Physiotherapy Conference Proceeding, 2024)
Introduction: Balance is a position to maintain a certain position in both static and dynamic conditions. Low balance performance is caused by age and cognitive function and increases fall risk. Objective: To determine the difference between static and dynamic postural balance in the elderly based on age categories of 45-90 years. Method: This research used an observational study method with a cross-sectional study approach. There were 220 people involved in this study and conducted by purposive sampling method. Static balance was measured by mCTSIB and dynamic balance used TUG. The cognitive function was measured by the MOCA-Ina questionnaire. The Anova test was conducted to analyse the data. Results: There was a significant difference between static and dynamic balance based on age category 45-90 years (p<0.05). No significant correlation between cognitive and dynamic balance in those aged 55-64 years, and no significant correlation in static balance in those aged more than 70 years. Conclusion: the age group over 70 years has the lowest dynamic balance (TUG) and static balance (MCTSIB).